2021
DOI: 10.1007/s00021-021-00639-2
|View full text |Cite
|
Sign up to set email alerts
|

On the Exponential Decay for Compressible Navier–Stokes–Korteweg Equations with a Drag Term

Abstract: In this paper, we consider global weak solutions to compressible Navier-Stokes-Korteweg equations with density dependent viscosities, in a periodic domain Ω = T 3 , with a linear drag term with respect to the velocity. The main result concerns the exponential decay to equilibrium of such solutions using log-sobolev type inequalities. In order to show such a result, the starting point is a global weak-entropy solutions definition, introduced in D. Bresch, A. Vasseur and C. Yu [12]. Assuming extra assumptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…We will base our proof of existence on this approach, with the specificity of taking an isothermal pressure law λρ (which leads to the use of energy with no definite sign, see below) and adding a dissipation term µρu. Note that in the recent paper [7] the authors have shown the exponential decay to equilibrium of global weak solutions of the Navier-Stokes-Korteweg system with such a dissipation term and for both barotropic and isothermal pressure laws.…”
Section: Introductionmentioning
confidence: 97%
“…We will base our proof of existence on this approach, with the specificity of taking an isothermal pressure law λρ (which leads to the use of energy with no definite sign, see below) and adding a dissipation term µρu. Note that in the recent paper [7] the authors have shown the exponential decay to equilibrium of global weak solutions of the Navier-Stokes-Korteweg system with such a dissipation term and for both barotropic and isothermal pressure laws.…”
Section: Introductionmentioning
confidence: 97%
“…In order to obtain the large time behavior (decay exponentially) of weak solutions, we obtain the relative entropy inequality between weak solutions and equilibrium solutions by introducing the relative entropy functional. Considering that the structure of reduced gravity two-and-a-half layer model is more complicated than compressible Navier-Stokes equations due to the presence of cross terms h 1 ∇h 2 , h 2 ∇h 1 , we need to estimate the cross term g 2 Ω (h 1 − R 1 )(h 2 − R 2 ) dx in relative entropy, which is different from the work of Bresch, Gisclon, Lacroix-Violet, Vasseur [7]. It should point out that g 2 Ω (h 1 − R 1 )(h 2 − R 2 ) dx can not be directly controlled by the cross term Ω ∇h 1 • ∇h 2 dx.…”
mentioning
confidence: 99%
“…Note that the method of Su-Li-Yao [26] can be applied to prove global existence of weak solution to the problem (1.1)-(1.2). The work of this paper is inspired by Bresch, Gisclon, Lacroix-Violet [6] and Bresch, Gisclon, Lacroix-Violet, Vasseur [7]. In order to obtain the large time behavior (decay exponentially) of weak solutions, we obtain the relative entropy inequality between weak solutions and equilibrium solutions by introducing the relative entropy functional.…”
mentioning
confidence: 99%
See 2 more Smart Citations